Improving English Communication for Specific Purposes Using Role-Play and Learning by Doing Techniques for the staff At The Samaya Resort Seminyak, Badung - I Putu Gede Satria Wiraharja; Dewa Ayu Dyah Pertiwi Putri; I Wayan Chandra Adyatma (Postgraduated Community Service Journal, 2023)
When the COVID-19 pandemic hit the tourism sector in Indonesia, especially in Bali, it experienced a quite drastic decline, so many workers were laid off. Not only decreased of tourist arrivals, but also decreased knowledge of English communication among workers, due to a lack of communication with guests staying at the hotel. Seminyak is a fashionable destination in Bali, especially its beaches and home to famous resorts, restaurants and boutiques. One of the most luxurious resorts in the Seminyak area is The Samaya Resort Seminyak, which is located on Jalan Laksmana Seminyak. English communication improvement training is a very important point in everyday life, especially in the world of hospitality work in improving speaking skills especially to guests staying at The Samaya Resort Seminyak. This can improve the quality of staff service to guests, and minimize miscommunication. Community Partnership Program activities in the form of teaching English using role-play techniques and learning English while practicing it directly (Learning by Doing) are appropriate activities for staff at The Samaya Resort Seminyak in developing and improving their communication skills using the language English with good and correct English grammar and pronunciation. The method applied in teaching English communication uses the role play and learning by doing methods. This English teaching activity is held for 1 (one) month for purposes, starting from 6 to 27 June 2023. From the teaching provided, the materials needed for staff at The Samaya Resort Seminyak are English material for specific related to service and services in the hotel according to the department of each staff. Based on the background that has been described, the main problems of partners are: 1). How do the staff at The Samaya Resort Seminyak master the grammar and pronunciation of English for Specific Purposes? 2). What are the results of the application of English learning techniques by Role-Play and Learning by Doing for Specific Purposes to the staff at the resort? To solve the problems faced by partners, an English teaching program was carried out using the role-play method and learning English while practicing it directly (Learning by Doing). The participants in this English training were 28 staff of The Samaya Resort Seminyak from all departments. For this reason, English will be taught at an intermediate level, with specific vocabulary and grammar according to their respective departments. This training will be held with meetings once a week for each department.